0329 Genome-wide association study for loci associated with digital dermatitis and pododermatitis circumscripta in Holstein cattle. (1st October 2016) - Oberbauer, A. M.; Danner, A. L.; Belanger, J. M.; Famula, T. R.; Heguy, J. M.
Abstract: Estimates of dairy cattle lameness range up to 50% of individuals in a herd being lame at any one time. The economic costs associated with lameness include premature culling, treatment, reduced reproductive fertility, and decreased milk while there are welfare concerns associated with the pain caused by lesions. Two of the most common lameness disorders are digital dermatitis and sole ulcers (pododermatitis circumscripta). Though the etiology of the two conditions differs greatly, heritability estimates for digital dermatitis and sole ulcers have been determined to be 0.4 and 0.3, respectively, signifying moderate heritability and amenable to genetic selection programs designed to reduce prevalence. To determine loci associated with each condition, genome wide association studies (GWAS) were conducted. Using diagnostic hoof trimming records, as well as digital dermatitis and sole ulcer sire EBVs from two commercial dairy farms in California, blood samples were taken from 150 selected Holstein cows representing 56 cases and 94 controls. DNA extracted from each cow was genotyped with the Illumina BovineHD BeadChip. Derived SNP genotypes were filtered such that only SNPs having call rates > 0.8, minor allele frequencies < 0.5, Hardy-Weinberg equilibria (HWE) P < 0.05, and Fisher's HWE P < 0.05 were included in the GWAS using Golden Helix SNP and Variation suite. Association testing using an additive, recessive, and dominant model for inheritance for each condition was performed using a correlation/trend test. Population stratification was corrected for using a principle component analysis. Haplotype block detection with linkage disequilibrium and association testing were also performed. Significant associations ( P genome < 0.05;-log10 > 1.3) were noted on chromosomes 3, 8, and 29 for digital dermatitis and a highly significant haplotype (× 2 -log10 P > 7.00, 95% CI) was noted on chromosome 29. Genome wide significance was reached on chromosomes 3 and 5 for sole ulcers though significant haplotype blocks were located on chromosomes 17, 25, and 28. An immune mediating candidate gene, TIRAP, on chromosome 29 was sequenced in three digital dermatitis cases and three controls, but no significant variations were noted. Future work will focus on further exploring the associated regions with the objective of identifying potential markers to aid in selecting breeding stock to reduce the incidence of both conditions.